Analisis Pengaruh Perubahan Lift Camshaft terhadap Daya dan Torsi pada Motor 4 Langkah 200cc - Andhika Novan Ramadhani; Bambang Irawan; Septyana Riskytasari; Nurhadi Nurhadi (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
Camshaft lift is an important parameter that determines the height of the valve lift, calculated from the valve position when it is completely closed to the fully open position. This component plays a crucial role in regulating the flow of the air and fuel mixture into the combustion chamber. This study aims to improve the performance of a 200cc 4-stroke motorcycle engine through camshaft lift modification, which is expected to affect the characteristics of engine torque and power. Modifications were carried out by designing two types of modified camshafts, namely series A and series B, as a comparison to the standard camshaft. The research method used is experimental testing using a dynamometer to measure engine torque and power at various speeds, ranging from 4,000 to 10,000 RPM. The data obtained were analyzed to determine the effect of each type of camshaft on engine performance. The test results show that the B series camshaft provides the most significant performance improvement compared to the standard and A series camshafts. At 7,500 RPM, the standard camshaft produces an average torque of 19.2 Nm, the A series camshaft 19.6 Nm, while the B series camshaft reaches 21.2 Nm. Meanwhile, at 10,000 RPM, the average power of the standard camshaft is recorded at 22.2 HP, the A series camshaft 24.1 HP, and the B series camshaft reaches 26.3 HP. This increase indicates that the camshaft lift modification is able to optimize the duration and height of the valve opening, so that the supply of the fuel and air mixture to the combustion chamber becomes more efficient. Thus, camshaft modification, especially the B series, is an effective and applicable solution in increasing the performance output of a 200cc motorcycle engine without having to make major changes to the overall engine structure.